Work-related fatal motor vehicle traffic crashes: Matching of 2010 data from the Census of Fatal Occupational Injuries and the Fatality Analysis Reporting System. (July 2016) - Byler, Christen; Kesy, Laura; Richardson, Scott; Pratt, Stephanie G.; Rodríguez-Acosta, Rosa L.
Highlights: For the first time, highway fatality cases from CFOI were matched to FARS. Matching joins data on risk factors, the crash, the worker, and the job. 953 of 1044 CFOI Highway cases for 2010 were successfully matched to FARS. CFOI identified 378 cases as "at-work" not identified as such in FARS. Compared to all matches, these tended to be non-transport workers or light vehicles. Abstract: Motor vehicle traffic crashes (MVTCs) remain the leading cause of work-related fatal injuries in the United States, with crashes on public roadways accounting for 25% of all work-related deaths in 2012. In the United States, the Bureau of Labor Statistics (BLS) Census of Fatal Occupational Injuries (CFOI) provides accurate counts of fatal work injuries based on confirmation of work relationship from multiple sources, while the National Highway Traffic Safety Administration (NHTSA) Fatality Analysis Reporting System (FARS) provides detailed data on fatal MVTCs based on police reports. Characterization of fatal work-related MVTCs is currently limited by data sources that lack either data on potential risk factors (CFOI) or work-relatedness confirmation and employment characteristics (FARS). BLS and the National Institute for Occupational Safety and Health (NIOSH) collaborated to analyze a merged data file created by BLS using CFOI and FARS data. A matching algorithm was created to link 2010 data from CFOI and FARS using date of incident and other case characteristics, allowing for flexibility in variables to address coding discrepancies. Using the matching algorithm, 953 of the 1044 CFOI "Highway" cases (91%) for 2010 were successfully linked to FARS. Further analysis revealed systematic differences between cases identified as work-related by both systems and by CFOI alone. Among cases identified as work-related by CFOI alone, the fatally-injured worker was considerably more likely to have been employed outside the transportation and warehousing industry or transportation-related occupations, and to have been the occupant of a vehicle other than a heavy truck. This study is the first step of a collaboration between BLS, NHTSA, and NIOSH to improve the completeness and quality of data on fatal work-related MVTCs. It has demonstrated the feasibility and value of matching data on fatal work-related traffic crashes from CFOI and FARS. The results will lead to improvements in CFOI and FARS case capture, while also providing researchers with a better description of fatal work-related MVTCs than would be available from the two data sources separately.